Vertical motion history of the island of O‘ahu, Hawaiian Islands, during the last two million years - Michael Toomey; Michael Sandstrom; Kimberly Huppert; Frederick Taylor; Thomas M. Cronin (Scientific Reports)
Abstract Intraplate hotspots deform the Earth’s lithosphere and shape the morphology of reef-bound islands. This paper constrains the depositional history of the coastal plain of O‘ahu, Hawaii over the past 2 million years using: (1) the strontium isotope stratigraphy of shallow water carbonates (e.g., corals, mollusks) sampled from a 337 m-long drill core; (2) model-predicted vertical motion of the Ewa Coastal Plain that incorporates displacements due to the flexural isostatic response of the lithosphere to loading of each volcano along the Hawaiian Chain as well as O‘ahu’s migration over the Hawaiian Swell. The results of this study indicate that O‘ahu subsided rapidly (~ 0.5 mm/yr) during the early Pleistocene via vertical displacements that our model largely attributes to crustal loading during construction of the Maui Nui complex. An abrupt slowing of subsidence during the past million years was likely caused by the relative progression of volcanism eastward to the island of Hawai‘i and O‘ahu’s migration over the crest of the swell. The morphologic transition from drown reef terraces offshore O‘ahu, to initiation of stable carbonate accumulation at the Ewa Coastal Plain, to uplifted carbonate shorelines at O‘ahu during the Pleistocene has been driven by progressive changes in vertical motion as the island has migrated away from the Hawaiian hotspot.